Construction and Application of Virtual Reality Geographic Information System - Ke Xi-Lin; Guo Qing-Sheng; Zhang Yue-Peng; Zhou Yan (Institute of Advanced Engineering and Science, 2014)
In the paper, virtual reality geographic information system is discussed and the related technologies involves the concept, characteristics, classification, key technology, and the main application and development situation , it analyzes the virtual reality technology and the necessity of combining geographical information system technology. As to the design and development process of the whole system, including the system's user interface, system requirements, the structure of the system design, system development model and related technology are discussed in this paper. In view of the virtual reality geographic information system technology, the 3-D (three Dimensional) spatial data acquisition, 3-D data model and digital terrain model and digital elevation model and 3-D data of level of detail model and the expression of 3-D data visualization, etc, on the basis of theoretical research, with the help of a professional virtual reality modeling software MultiGen Creator, it builts the scenic spot of the 3-D environment. And it presents the virtual scene modeling process on the basis of MultiGenCreator complex modeling, the implementation plan, scene modeling method are also given out. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.4872